2022
DOI: 10.1108/tqm-05-2022-0164
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Industry 4.0 and Total Productive Maintenance for global sustainability

Abstract: PurposeThe integration of Total Productive Maintenance (TPM) and Industry 4.0 (I4.0) is an emerging model, and the global pressure of various stakeholders raises scepticism of any emerging model towards providing sustainability. Therefore, this research aims to identify and rank the potential significant drivers of an integrated model of I4.0 and TPM to guide manufacturing enterprises towards sustainability.Design/methodology/approachThis research follows a four-phase methodology including literature review an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Various theories as well as research works in the past support the integration of OPEX strategies with digital technologies from a SMEs business perspective. Due to the interplay between IE 4.0 and OPEX, the sustainable production capabilities of SMEs have gradually improved (Leong et al, 2020;Samadhiya et al, 2022). Also, past researchers suggested that OPEX has the potential to arrange business and operations in a faster and more efficient manner and can enhance its profitability and competitive advantages (Kamble et al, 2019;Wahab et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Various theories as well as research works in the past support the integration of OPEX strategies with digital technologies from a SMEs business perspective. Due to the interplay between IE 4.0 and OPEX, the sustainable production capabilities of SMEs have gradually improved (Leong et al, 2020;Samadhiya et al, 2022). Also, past researchers suggested that OPEX has the potential to arrange business and operations in a faster and more efficient manner and can enhance its profitability and competitive advantages (Kamble et al, 2019;Wahab et al, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Due to the interplay between IE 4.0 and OPEX, the sustainable production capabilities of SMEs have gradually improved (Leong et al. , 2020; Samadhiya et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent review studies show that existing body of knowledge on the topic of sustainable maintenance within the domain of Industry 4.0 [6] and Industry 5.0 [22], i.e., Maintenance 5.0, is mostly concerned [23] with resilient, worker-in-the-loop and human-inthe-loop [11] maintenance research. It places the wellbeing of the worker at the centre of the production process, enabling the use advanced technologies that provide prosperity beyond jobs.…”
Section: Related Researchmentioning
confidence: 99%
“…Rhetorically, SM goes beyond the traditional understanding of maintenance as a mere technical activity of condition monitoring, maintenance activities and planning [5]. In fact, it recognizes the interconnectedness between human activities, asset management and the environment, acknowledging the importance of sustainability challenges [6]. Such a holistic approach provides (1) a shift in traditional perception of maintenance as a "necessary evil" to "value-added activity" [7]; (2) transition from a short-term financial benefit to a long-term perspective; and (3) better understanding of the life cycle impacts of maintenance activities [8].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Considering the lean part, the present paper adopts pull production and total productive maintenance, which are two well-known lean manufacturing techniques [28]. In this respect, pull production is enabled through ad hoc policies, such as Base Stock [29,30], while total productive maintenance is integrated through predictive maintenance policies, e.g., condition-based maintenance, that seek to minimize maintenance costs and improve the availability of processing machines [31]. The implemented ad hoc policies are frequently employed in the real-world industry and the academic literature [32,33].…”
Section: Introductionmentioning
confidence: 99%